Canva-Based Logo and Packaging Design Training for the "Tani Maju" Farmer Group of Bantarkulon - Dewi, Alfa Yuliana; Septiady, R. Kurniawan Dwi; Faradisi, Firman; Nur, Achmad Vandian; Waznah, Urmatul; Fajriyah, Nuniek Nizmah; Harismah, Kun; Nuryulia, Aflit; Sofyan, Aan (Jurnal Pengabdian Masyarakat, 2025)
Purpose: This study aimed to empower the "Tani Maju" Farmer Group by improving their product visualization through Canva-based logo and packaging design training, addressing their limited design skills that hinder market competitiveness. Method: A participatory action research (PAR) approach guided four interactive sessions. Data were collected via pre- and post-training questionnaires (5-point Likert scale) and analysis of design outputs, with paired t-tests and thematic analysis applied. Practical Applications: Findings show that accessible digital tools like Canva enhance branding for agricultural MSMEs, enabling cost-effective, professional packaging design, improving marketability and sales potential.  Conclusion: Training significantly boosted participants’ design knowledge, skills (up to 122.22%), and confidence (up to 153.33%). The study demonstrates how digital literacy empowers rural communities, strengthens local economies, and bridges the gap between traditional farming and modern marketing.